B-box containing protein 1 from Malus domestica (MdBBX1) is involved in the abiotic stress response - Yaqing Dai; Ying Lu; Zhou Zhou; Xiaoyun Wang; Hongjuan Ge; Qinghua Sun (PeerJ, 2022)
B-box proteins (BBXs), which act as transcription factors, mainly regulate photomorphogenesis. However, the molecular functions underlying the activity of plant BBXs in response to abiotic stress remain largely unclear. In this investigation, we found that a BBX from Malus domestica (MdBBX1) was involved in the response to various abiotic stresses. The expression of MdBBX1 was significantly upregulated in response to abiotic stresses and abscisic acid (ABA). Recombinant MdBBX1 increased stress tolerance in Escherichia coli cells. In addition, overexpression of MdBBX1 in Arabidopsis decreased sensitivity to exogenous ABA, resulting in a germination rate and root length that were greater and longer, respectively, than those of wild-type (WT) plants. Moreover, the expression of ABI5 was decreased in MdBBX1-overexpressing lines under ABA treatment. After salt and drought treatments, compared with the WT plants, the MdBBX1 transgenic plants displayed enhanced tolerance and had a higher survival rate. Furthermore, under salt stress, increased proline (PRO) contents, decreased levels of malondialdehyde (MDA), increased activity of antioxidant enzymes (superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX)) and decreased accumulation of reactive oxygen species (ROS) were observed in the MdBBX1-overexpressing plants. Overall, our results provide evidence that MdBBX1 might play a critical role in the regulation of abiotic stress tolerance by reducing the generation of ROS.